A primer to metabarcoding surveys of Antarctic terrestrial biodiversity. Issue 1 (13th September 2016) - Czechowski, Paul; Clarke, Laurence J.; Cooper, Alan; Stevens, Mark I.
Abstract: Ice-free regions of Antarctica are concentrated along the coastal margins but are scarce throughout the continental interior. Environmental changes, including the introduction of non-indigenous species, increasingly threaten these unique habitats. At the same time, the unique biotic communities subsisting in isolation across the continent are difficult to survey due to logistical constraints, sampling challenges and problems related to the identification of small and cryptic taxa. Baseline biodiversity data from remote Antarctic habitats are still missing for many parts of the continent but are critical to the detection of community changes over time, including newly introduced species. Here we review the potential of standardized (non-specialist) sampling in the field (e.g. from soil, vegetation or water) combined with high-throughput sequencing (HTS) of bulk DNA as a possible solution to overcome some of these problems. In particular, HTS metabarcoding approaches benefit from being able to process many samples in parallel, while workflow and data structure can stay highly uniform. Such approaches have quickly gained recognition and we show that HTS metabarcoding surveys are likely to play an important role in continent-wide biomonitoring of all Antarctic terrestrial habitats.